2018
DOI: 10.1016/j.biopsycho.2018.10.006
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to traumatic events in childhood predicts cortisol production among high risk pregnant women

Abstract: Childhood exposure to traumatic events has a profound and disruptive impact on mental and physical health, including stress physiology. In the current study, we evaluate 90 pregnant women at risk for preterm delivery and assess the association between history of exposure to traumatic events and hair cortisol concentrations, an integrated measure of cortisol production. Exposure to more traumatic events in childhood and in adulthood independently predicted elevated hair cortisol concentrations in pregnancy. Not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
42
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(45 citation statements)
references
References 70 publications
(116 reference statements)
1
42
2
Order By: Relevance
“…As mentioned above, recent studies found close links between trauma exposure across the lifespan and long-term regulation of HPA axis activity (Steudte-Schmiedgen et al, 2016; Pervanidou et al, 2017). Interestingly, initial cross-sectional HCC research supports the notion of a relationship between lifetime trauma exposure, childhood abuse, and HCC during pregnancy (Schreier et al, 2015, 2016; Swales et al, 2018). A prospective study further confirmed associations between maternal lifetime trauma history, HCC reflecting the third trimester of pregnancy, and subsequent infant negative affectivity at the age of 6 month (Bosquet Enlow et al, 2017).…”
Section: Introductionmentioning
confidence: 92%
“…As mentioned above, recent studies found close links between trauma exposure across the lifespan and long-term regulation of HPA axis activity (Steudte-Schmiedgen et al, 2016; Pervanidou et al, 2017). Interestingly, initial cross-sectional HCC research supports the notion of a relationship between lifetime trauma exposure, childhood abuse, and HCC during pregnancy (Schreier et al, 2015, 2016; Swales et al, 2018). A prospective study further confirmed associations between maternal lifetime trauma history, HCC reflecting the third trimester of pregnancy, and subsequent infant negative affectivity at the age of 6 month (Bosquet Enlow et al, 2017).…”
Section: Introductionmentioning
confidence: 92%
“…Childhood adversity may contribute to maladaptive alterations in stress physiology during pregnancy, such as greater maternal HPA axis dysregulation evidenced by both elevated and suppressed concentrations of cortisol during pregnancy (Bowers & Yehuda, 2016; Schreier, Enlow, Ritz, Gennings, & Wright, 2015; Swales et al, 2018). Maternal report of childhood maltreatment is linked to elevations in hair cortisol concentrations during pregnancy (Schreier et al, 2015) and has been found to amplify the impact of women's more proximal exposure to adulthood traumatic events prior to pregnancy on prenatal hair cortisol concentrations (Swales et al, 2018). Further, childhood maltreatment also is associated with alterations in placental–fetal stress physiology, including significantly steeper increases in placental CRH across gestation (Buss et al, 2017; Moog et al, 2018).…”
Section: Adversity Antecedents Of Prenatal Maternal Stress and Mentalmentioning
confidence: 99%
“…Thus, pregnancy is a sensitive period when the dyad is vulnerable to the effects of adversity; however, mothers and infants also are especially receptive to salutary influences. Research has found that maternal exposure to adversity prior to conception (particularly during her childhood) can have transformative neurobiological and epigenetic effects that may be biologically embedded and transmitted to the fetus (Swales et al, 2018; Yehuda & Meaney, 2018). Compared to women without early-life adversity and mental health problems prior to pregnancy, pregnant women with a history of adversity and mental health problems may experience more risks to their mental health and more disruptions to their prenatal stress physiology.…”
mentioning
confidence: 99%
“…If stress is related to HPA axis output, and cortisol can be measured in hair, it follows that stress experienced during pregnancy should be related to hair cortisol concentrations. Indeed, self‐reported prenatal stress and anxiety, and even stress experienced in childhood such as preconception stress, trauma exposure, and childhood physical and/or sexual abuse have all been associated with elevated hair cortisol concentrations during pregnancy (Hoffman, Mazzoni, Wagner, Laudenslager, & Ross, ; Kalra, Einarson, Karaskov, Van Uum, & Koren, ; Orta et al, , ; Schreier et al, ; Swales et al, ). On the other hand, no associations were found between hair cortisol concentrations and maternal depression in the second trimester, pregnancy‐related anxiety, somatization, or stress symptoms in other research (Braig et al, ; Kramer et al, ; Scharlau et al, ; Wikenius et al, ).…”
Section: Introductionmentioning
confidence: 99%